Updated Evaluation of Laparoscopic vs. Open Appendicectomy During Pregnancy: A Systematic Review and Meta-Analysis - Zhang, Jia; Wang, Miye; Xin, Zechang; Li, Ping; Feng, Qingbo (Frontiers in Surgery, 2021)
To explore the updated evaluation about the obstetrical and perioperative outcomes of laparoscopic appendicectomy (LA) for pregnancy appendicitis compared with open appendicectomy (OA). Two reviewers independently searched the PubMed, the Cochrane Central Register of Controlled Trials, EMBASE, and Web of Science databases to screen eligible studies up to December 2020. Only clinical researches, no < 10 cases for LA and OA group were included. Twenty retrospective studies with 7,248 pregnant women, evaluating LA and OA in surgical and obstetrical outcomes, were included. The weighted mean difference (WMD) with 95% CI and odds ratio (OR) was used to compare continuous and dichotomous variables. It seems LA was connected with significantly shorter hospital time and lower wound infection [mean difference (MD), −0.57 days; 95% CI, −0.96 to −0.18; p = 0.004 and OR, 0.34; 95% CI, 0.18 to 0.62; p = 0.0005, respectively]. The incidence of fetal loss after LA was higher than OA (OR,1.93; 95% CI, 1.39–2.69; p < 0.0001). It was almost similar in the rate of preterm delivery (OR, 0.80; 95% CI, 0.48 to 1.34; p = 0.40) and other perioperative and obstetrical complications (p > 0.05). Our results indicated that the occurrence of fetal loss after LA should not be ignored. Caution, skillful operation, and thoroughly informed consent about the advantages and disadvantages of laparoscopy are necessary. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/#recordDetails, identifier: CRD42021233150.